Digital Marketing Communication of Banyunibo Temple Area Through Tiktok - Prasetyo Nugroho Saputro, Eko; Wahyu Widiarti, Pratiwi; Disyacitta, Fikri; Ekawati, Ratna (Lektur: Jurnal Ilmu Komunikasi, 2025)
The Banyunibo Temple area holds significant potential that requires effective digital marketing communication to introduce its value to a broader audience. To support this digital marketing communication strategy, suitable media platforms are essential for quickly and efficiently conveying messages to the public. This research aimed to develop a digital marketing communication medium in the form of TikTok to promote the Banyunibo Temple area in Bokoharjo Village. The study employed a Research and Development (RD) methodology. The findings demonstrate that TikTok content was successfully developed as a digital marketing tool for the Banyunibo Temple Area. The stages of development follow the ADDIE model (Analysis, Design, Develop, Implement, and Evaluate). However, the research only progressed through the implementation stage. The developed content was evaluated by two media experts and a social media manager from the Banyunibo Temple area. The evaluation feedback was used to revise the product, ensuring its effectiveness as a digital marketing communication medium. These revisions significantly improved the content, leading to a successful implementation phase where the TikTok posts achieved considerable viewership, averaging over 230 views per post.Keywords: Banyunibo, Tiktok, Media, Digital Marketing Communication.